2021
DOI: 10.1016/j.adro.2021.100745
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Knowledge-Based Treatment Planning Model for Cardiac-Sparing Lung Radiation Therapy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Our results first showed that creation of an Auto model from our manually optimised plans using 21 patient plans is feasible. Historically, the number of cases required to create an automated RapidPlan model varied, ranging from 20 to almost 200 (11,(19)(20)(21)(22)(23)(24), with number of cases likely at least partially dependent on the subsite being assessed. Ueda et al (20) suggested that only 20 cases might be enough to create a model if large variations existed in the (25).…”
Section: Discussionmentioning
confidence: 99%
“…Our results first showed that creation of an Auto model from our manually optimised plans using 21 patient plans is feasible. Historically, the number of cases required to create an automated RapidPlan model varied, ranging from 20 to almost 200 (11,(19)(20)(21)(22)(23)(24), with number of cases likely at least partially dependent on the subsite being assessed. Ueda et al (20) suggested that only 20 cases might be enough to create a model if large variations existed in the (25).…”
Section: Discussionmentioning
confidence: 99%